Multidisciplinary management of acromegaly: A consensus - Giustina, Andrea; Barkhoudarian, Garni; Beckers, Albert; Ben-Shlomo, Anat; Biermasz, Nienke; Biller, Beverly; Boguszewski, Cesar; Bolanowski, Marek; Bollerslev, Jens; Bonert, Vivien; Bronstein, Marcello D.; Buchfelder, Michael; et al. (Reviews in Endocrine & Metabolic Disorders, 2020)
The 13th Acromegaly Consensus Conference was held in November 2019 in Fort Lauderdale, Florida, and comprised acromegaly experts including endocrinologists and neurosurgeons who considered optimal approaches for multidisciplinary acromegaly management. Focused discussions reviewed techniques, results, and side effects of surgery, radiotherapy, and medical therapy, and how advances in technology and novel techniques have changed the way these modalities are used alone or in combination. Effects of treatment on patient outcomes were considered, along with strategies for optimizing and personalizing therapeutic approaches. Expert consensus recommendations emphasize how best to implement available treatment options as part of a multidisciplinary approach at Pituitary Tumor Centers of Excellence.
CRIS-Team Scopus Importer:2020-09-25
Keywords: Acromegaly; Consensus; Medical therapy; Multidisciplinary management; Pituitary tumor centers of excellence; Radiotherapy; Surgery